THE ROLE OF SPORTS IN HIGHER EDUCATION - Hayitov, Jumaqul Negmatovich (Educational Research in Universal Sciences, 2023)
This article provides a summary of the role of sport in higher education. The organization of a healthy lifestyle in every educational institution is one of the most important functions.